The Mediating Effect of Psychological Capital Between Two-Way Social Support and Academic Resilience Among Chinese Undergraduate Nursing Students - Jingjing Zhang; Feiyue Li; Wenjing Li; Feifei Xiong; Lingfan Zhou; Shimeng Dai; Tao Wei; Chaoqun Dong (Florence Nightingale Journal of Nursing, 2026)
AIM: This study examined the mediating role of psychological capital between two-way social support and academic resilience among undergraduate nursing students. METHODS: This cross-sectional study used convenience sampling to conduct a questionnaire survey among 1256 undergraduate nursing students in China in December 2022. The College Student Academic Resilience Scale, the Two-way Social Support Scale, and the Positive Psychological Capital Scale were used to collect the research data. To examine complex relationships among variables, correlation analysis and structural equation modeling were applied. The sample size met structural equation modeling requirements, and the bootstrap method was used to test the mediating effect of psychological capital and its 95% confidence interval. RESULTS: Two-way social support positively predicted psychological capital (β = 0.792, 95% CI [0.657, 0.927], p < .001), which in turn positively predicted academic resilience (β = 0.869, 95% CI [0.814, 0.924], p < .001). No direct effect was found between two-way social support and academic resilience (β = −0.005, 95% CI [−0.107, 0.097], p = .903). Psychological capital fully mediated this relationship with a significant indirect effect (β = 0.688, 95% CI [0.638, 0.726], p < .001). CONCLUSION: Psychological capital fully mediates how two-way social support enhances academic resilience. Integrating psychological capital development and structured social support into nursing education may effectively promote student resilience. Cite this article as: Zhang, J., Li, F., Li, W., Zhou, L., Xiong, F., Dai, S., Wei, T., & Dong, C. (2026). The mediating effect of psychological capital between two-way social support and academic resilience among chinese undergraduate nursing students. Florence Nightingale Journal of Nursing, 34, 0403, doi: 10.5152/FNJN.2026.25403.